Few-layer HfS(2) transistors - Kanazawa, Toru (Sci Rep, 2016)
HfS(2) is the novel transition metal dichalcogenide, which has not been experimentally investigated as the material for electron devices. As per the theoretical calculations, HfS(2) has the potential for well-balanced mobility (1,800 cm(2)/V·s) and bandgap (1.2 eV) and hence it can be a good candidate for realizing low-power devices. In this paper, the fundamental properties of few-layer HfS(2) flakes were experimentally evaluated. Micromechanical exfoliation using scotch tape extracted atomically thin HfS(2) flakes with varying colour contrasts associated with the number of layers and resonant Raman peaks. We demonstrated the I-V characteristics of the back-gated few-layer (3.8 nm) HfS(2) transistor with the robust current saturation. The on/off ratio was more than 10(4) and the maximum drain current of 0.2 μA/μm was observed. Moreover, using the electric double-layer gate structure with LiClO(4):PEO electrolyte, the drain current of the HfS(2) transistor significantly increased to 0.75 mA/μm and the mobility was estimated to be 45 cm(2)/V·s at least. This improved current seemed to indicate superior intrinsic properties of HfS(2). These results provides the basic information for the experimental researches of electron devices based on HfS(2).